Peningkatan Pemahaman Mahasiswa Akuntansi Tentang Perpajakan Manufaktur Melalui Studi Lapangan di PT. Industri Jamu dan Farmasi Sido Muncul Tbk. - Winny Lian Seventeen; Prety Kurmiati Sari; Yose Arta Melvia; Indah Dwi Lestari (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
**Paraphrased Text (158 words):** Tax management is one of the most complex aspects of financial oversight for manufacturing companies, particularly under Indonesia’s self-assessment taxation system. Taxpayers are required to independently calculate, pay, and report their tax obligations. However, there is a significant gap between academic tax theory and real-world corporate practices, leaving many accounting students with limited understanding of how large manufacturing firms handle taxes. To address this, a community service program enabled 37 accounting students to conduct a field study at PT Industri Jamu dan Farmasi Sidomuncul Tbk in Semarang, Central Java. The students visited the production facility, engaged in discussions with company representatives, and reviewed the company’s 2025 Annual Report published on the Indonesia Stock Exchange. The initiative successfully provided students with practical, contextual knowledge of tax obligations in manufacturing companies, especially regarding tax compliance as part of good corporate governance. However, complex areas such as Value Added Tax (VAT) and Income Tax Article 21 remain challenging. The program proved effective and is recommended to be held regularly with deeper exploration of intricate tax processes.